Endodontic Management of Mandibular Second Molar with Middle Distal Canal: Management Endodontik pada Gigi Geraham Kedua Mandibula dengan Saluran Distal Tengah - Jessica Komala; Widi Prasetia; Wandania Farahanny (Dentika: Dental Journal, 2024)
Mandibular second molar is often associated with variations in root canal morphology. Despite the intricate association, the occurrence of middle distal canal in endodontic literature is limited, with an incidence of 0.2% to 3%. Therefore, this study presents a case report describing a clinical situation in mandibular second molar that shows four canals, opening into different apical foramens. A 30-year-old male patient came to the Rumah Sakit Gigi dan Mulut of Universitas Sumatera Utara with the main complaint of intermittent pain in the lower right tooth persisting for two days. The results of clinical examination of the lower right second molar labeled as #47, showed a temporary filling, while radiography indicated widened periodontal ligament space and termination of lamina dura. After receiving informed consent, root canal therapy was carried out, and a direct resin composite onlay was selected for final restoration. To locate and treat hidden and unusual anatomy, dentists are often required to possess a comprehensive understanding of internal dental anatomy and use modern instruments, such as the dental operating microscope and ultrasonic tips. In certain clinical, direct resin composite onlay restorations can represent a valid alternative to traditional indirect restorations. In conclusion, this study shows that a comprehensive understanding of the potential variances in the internal anatomy of human teeth is essential to achieving successful outcomes in endodontic therapy.